2005
DOI: 10.1142/s0192415x05002709
|View full text |Cite
|
Sign up to set email alerts
|

Yukmijihwang-Tang Derivatives Enhance Cognitive Processing in Normal Young Adults: A Double-Blinded, Placebo-Controlled Trial

Abstract: Yukmijihwang-tang (YMJ), also known as Luweidihuang-tang in China, has been widely used as a general herbal tonic for hundreds of years in many Asian countries. This study examines whether YMJ derivatives (YMJd) enhance cognitive ability in normal human subjects and discusses its potential as treatment for dementia patients with deficient cognitive ability. Subjects were divided into two groups, the placebo-treated group (n = 15) and the YMJd-treated group (n = 20). K-WAIS tests, a Korean version of an individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Previous studies have reported the pharmacological efficacy of PM012 in various AD models. PM012 was shown to have a potent protective effect against ibotenic acid-induced cell damage and cognitive deficits [29]. In addition, PM012 treatment accelerated information processing and enhanced cognitive abilities in normal human subjects [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported the pharmacological efficacy of PM012 in various AD models. PM012 was shown to have a potent protective effect against ibotenic acid-induced cell damage and cognitive deficits [29]. In addition, PM012 treatment accelerated information processing and enhanced cognitive abilities in normal human subjects [29].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of these medicines have been demonstrated scientifically [28]. Among them, the herbal formula PM012 (also known as Yukmijihwang-tang derivatives) is one of the most extensively studied for its effect on dementia [29]. PM012 has a significant effect on memory enhancement, the expression of genes associated with preventing neuronal degeneration, and genes associated with neuronal growth [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hachimijiogan and goshajinkigan warm the extremities and the body [1,2]. Moreover, rokumigan [14] and hachimijiogan [15] have shown usefulness for memory enhancement, improvement of precognitive abilities, prevention of neuronal degeneration [16], and protection from ischemia/reperfusion-induced renal injury [17].…”
Section: Issn: 2378-1343mentioning
confidence: 99%
“…YMJ prevents the deterioration of learning and memory ability in senescent accelerated mice and hydrocortisone-treated mice [123] YMJ reverses scopolamine-induced and p-chloroamphetamine-induced amnesia in rats. YMJ cause significant reversal of ibotenic acid-induced deficit in learning and memory [124,125] YMJ derivatives enhance cognitive ability in normal human subjects, accelerates the speed of information processing and enhances cognitive ability [126] 7.…”
Section: Korean Herbal Formulations For Cognitionmentioning
confidence: 99%